2014
DOI: 10.1364/ol.39.000466
|View full text |Cite
|
Sign up to set email alerts
|

1617  nm emission control of an Er:YAG laser by a corrugated single-layer resonant grating mirror

Abstract: A resonant grating mirror (RGM) that combines a single layer planar waveguide and a subwavelength grating is used to simultaneously control the beam quality, the spectral bandwidth, and the polarization state of an Er:YAG laser. This simple device is compared to classical methods using several intracavity components: an etalon for wavelength selection, a thin film polarizer for polarization selection, and an aperture for spatial filtering. It is demonstrated that the RGM provides the same polarization purity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…RWG mirrors can be designed to achieve a narrower linewidth and higher polarization selectivity compared to conventional narrowband mirrors, such as Fabry–Perot cavities. Moreover, they also provide lower thermal noise and lower mechanical losses thanks to their lower overall thickness .…”
Section: Applicationsmentioning
confidence: 99%
“…RWG mirrors can be designed to achieve a narrower linewidth and higher polarization selectivity compared to conventional narrowband mirrors, such as Fabry–Perot cavities. Moreover, they also provide lower thermal noise and lower mechanical losses thanks to their lower overall thickness .…”
Section: Applicationsmentioning
confidence: 99%
“…The waveguide coupling synchronism condition now writes from (1) Λ = λ/n e , but the propagation length L, which determines the angular width, now depends on the radiation coefficient α and, per symmetry, also and notably on the second order intra-guide coupling coefficient κ between the forward and backward propagating mode which tends to reflect it back, thus to decrease the propagation length in the waveguide and consequently to widen the angular width of resonant reflection regardless of its spectral width. This property of resonant reflection under normal incidence permits to adjust the angular and wavelength spectral widths essentially independently unlike in the well known usual case of oblique incidence as used by Aubourg et al to improve the beam quality of an Er:YAG laser [11] and first demonstrated in a laser by Avrutsky [12]. This combined effect of α and κ implies that no simple analytical expression can be given for L, thus for Δθ, in the normal incidence case, the more so as the phenomenological parameters α and κ loose their usefulness as they vary substantially with the optogeometrical parameters in the neighborhood of normal incidence.…”
Section: Operation Principle In a 1-d Waveguide Gratingmentioning
confidence: 99%
“…There have been a number of studies investigating the potential of GMRFs for laser frequency stabilization, first on dye lasers [33][34][35] and large-area or disk semiconductors lasers [36,37], then on fibered [38][39][40][41] or solid-state lasers [42,43]. Despite a clear potential, only few ECDLs using GMRF as external mirror have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%